Dip-coating methods for carbon membrane fabrication: Effects of coating-carbonization-cycles on Hydrogen separation prepared from BTDA-TDI/MDI (P-84) polyimide blends with Nanocrystalline cellulose (NCC) - Norazlianie, Sazali; Mohd Syafiq, Yusoff; Ihsan Naiman, Ibrahim; Haziqatulhanis, Ibrahim; Mohd Nizar, Mhd Razali; Wan Norharyati, Wan Salleh (Springer, Singapore, 2019)
In this paper depicts the manufacture and assessment of tubular carbon membrane equipped from BTDA-TDI/MDI (P-84) polyimide mixes with Nanocrystalline cellulose (NCC). Given earlier investigations, we planned the theory that tubular carbon membrane performance could impose constraints by controlling the carbonization conditions which directed with a heating rate of 3°C/min, a final temperature of 800°C and adjustment time of 300°C. The principal purpose of this examination is to acquaint successful dip-coating strategies with produce superior tubular carbon membrane. The coating-carbonization cycles (1, 2, 3, and 4 times) have been considered. This methodology empowers quick and straightforward assessment of dip-coating techniques to yields high separation performance. Gas separation performance of the carbon membranes was adequately carried out by a single gas permeation experiment of H2, and N2 to explore the transport component in the carbon membrane separation process. In this case, the most elevated selectivity of 434.68±1.39 for H2/N2; side by side with H2 permeance of 1399.66±5.22 GPU shall accomplish by employing two coating-carbonization-cycles.